The Role of Profitability in Moderating the Influence of Company Size, Company Activities, Board of Directors, and Audit Committee on Disclosure of Sustainability Reports in Non-Financial Companies Registered on BEI and Publishing Sustainability Reports for 2018-2020 - Ario Satria; Yuliusman; Susfa Yetti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to collect empirical evidence regarding the influence of company size, performance, board of directors and audit committee on sustainability reporting, profitability as a moderating variable. This research is quantitative research using secondary data obtained from the Indonesian Stock Exchange. The subjects of this research include non-financial companies listed on the IDX in 2018-2020. The sampling method uses a purposive sampling method with the criteria that non-financial companies have registered and published financial reports and sustainability reports for the 2018-2020 period. The research sample consisted of 32 companies over 3 years, so the total sample for this research was 96. The data analysis technique used was descriptive statistics and moderate regression analysis (MRA) using SPSS version 21 software with a significance level of 5%. The results of this research show that different company sizes and audit committees have an effect on sustainability reporting, while company performance and the board of directors have no effect on sustainability reporting for Sustainable Development. The profit variable cannot adjust the influence of company size, company performance, board of directors and audit committee on sustainability reporting